2018
DOI: 10.18061/bhac.v2i1.6360
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Life Lessons: When Millennials Fail

Abstract: Background: Students who fail may face feelings of diminished self-perception, decreased sense of achievement, and experience negative emotions or moods such as: guilt, embarrassment, thoughts of reoccurring failure, feeling of letting others down or disappointing teachers and parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The authors reported that fear, including fear of failure, can manifest itself in various behaviors, including missed classes, frequent illnesses, little or no class engagement, and missed assignments (Bledsoe and Baskin 2014). Poor academic performance for URM students in particular has large ramifications that can include loss of financial support to complete their educational pursuits (Ramirez et al 2018). Additionally, Ramirez and colleagues (2018) shared that failure can lead to poor self-concept, embarrassment, insecurities about career pathways, and "fear of letting others down. "…”
Section: Fear Of Failurementioning
confidence: 99%
“…The authors reported that fear, including fear of failure, can manifest itself in various behaviors, including missed classes, frequent illnesses, little or no class engagement, and missed assignments (Bledsoe and Baskin 2014). Poor academic performance for URM students in particular has large ramifications that can include loss of financial support to complete their educational pursuits (Ramirez et al 2018). Additionally, Ramirez and colleagues (2018) shared that failure can lead to poor self-concept, embarrassment, insecurities about career pathways, and "fear of letting others down. "…”
Section: Fear Of Failurementioning
confidence: 99%
“…The authors reported that fear, including fear of failure, can manifest itself in various behaviors, including missed classes, frequent illnesses, little or no class engagement, and missed assignments (Bledsoe and Baskin 2014). Poor academic performance for URM students in particular has large ramifications that can include loss of financial support to complete their educational pursuits (Ramirez et al 2018). Additionally, Ramirez and colleagues (2018) shared that failure can lead to poor self-concept, embarrassment, insecurities about career pathways, and "fear of letting others down. "…”
Section: Fear Of Failurementioning
confidence: 99%